Peptides containing blocks of different charge densities facilitate cell uptake of oligonucleotides. Issue 14 (4th March 2015) - Zhou, Jihan; Li, Dong; Su, Cuicui; Wen, Hao; Du, Quan; Liang, Dehai
Abstract : The complexes formed by block peptides and oligonucleotides were stable in serum with improved cell uptake. Abstract : Polyelectrolyte complexes (PECs) are of great importance in drug delivery and gene therapy. The density and the distribution of the charges are key parameters of a polyelectrolyte, determining the structure of the complex and the kinetics of the complexation. Using peptides of precisely-controlled charge density as model molecules, we showed that the presence of weakly-charged peptides, (KGGG)5 or (KGKG)5, did not affect the complexation of highly-charged peptides (KKKK)5 with 21 bp oligonucleotides. However, peptide containing blocks of different charge densities, such as (KKKK)5 - b -(KGGG)5 or (KKKK)5 - b -(KGKG)5, exhibited superior performance during complexation. With a relatively uniform small size, the complex was also stable in serum. More importantly, the cellular uptake of the complex was greatly enhanced by a ratio of 40–60%, compared to that of the complex formed by uniformly-charged peptides. We attributed the improvement to the structure of the complex, in which the highly-charged blocks form the core with the oligonucleotide whilst the weakly-charged blocks dangle outside, preventing the complexes from further aggregation.